2015
DOI: 10.1016/j.paid.2015.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Explaining workplace delinquency: The role of Honesty–Humility, ethical culture, and employee surveillance

Abstract: a b s t r a c tIn this research the effects of personality and organizational characteristics on workplace delinquency were investigated. In a sample of 455 respondents from a wide variety of organizations, two personality traits, HEXACO Honesty-Humility and Conscientiousness, and two organizational characteristics, ethical culture and employee surveillance, explained a significant amount of variance in workplace delinquency. No interaction effects between personality and organizational practices in the explan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 29 publications
(30 reference statements)
3
59
1
1
Order By: Relevance
“…In fact, SVO shares significant overlap with HEXACO Honesty‐Humility (and with Big Five Agreeableness; Hilbig, Glöckner, & Zettler, ). Honesty‐Humility describes the tendency to be fair and honest (Ashton & Lee, ) and is associated with various socially desirable behaviours, such as a lower likelihood to sexually harass someone (Lee, Gizzarone, & Ashton, ) or to be delinquent and criminal (De Vries & Van Gelder, , ), and with increased interpersonal cooperation (Thielmann & Hilbig, ). Similarly, decades of research have shown that SVO reliably predicts cooperation not only in social dilemmas (Balliet et al, ) but also across a broad range of natural settings (e.g.…”
Section: Social Value Orientation and Cooperation In Social Dilemmasmentioning
confidence: 99%
“…In fact, SVO shares significant overlap with HEXACO Honesty‐Humility (and with Big Five Agreeableness; Hilbig, Glöckner, & Zettler, ). Honesty‐Humility describes the tendency to be fair and honest (Ashton & Lee, ) and is associated with various socially desirable behaviours, such as a lower likelihood to sexually harass someone (Lee, Gizzarone, & Ashton, ) or to be delinquent and criminal (De Vries & Van Gelder, , ), and with increased interpersonal cooperation (Thielmann & Hilbig, ). Similarly, decades of research have shown that SVO reliably predicts cooperation not only in social dilemmas (Balliet et al, ) but also across a broad range of natural settings (e.g.…”
Section: Social Value Orientation and Cooperation In Social Dilemmasmentioning
confidence: 99%
“…Furthermore, the HEXACO model, through its incorporation of an additional honestyhumility dimension and its reconfiguration of Big Five agreeableness and emotional stability (see provides incremental prediction in important outcome variables that are less well captured by the Big Five model (Ashton & Lee, 2008;Ashton et al, 2014;De Vries, Tybur, Pollet, & Van Vugt, 2016b). In particular, the ability of the honesty-humility factor to incrementally predict counterproductive work behaviour is particularly appealing for employers (De Vries & Van Gelder, 2015;Lee, Ashton, & De Vries, 2005;Louw, Dunlop, Yeo, & Griffin, 2016;Marcus, Lee, & Ashton, 2007;Oh, Lee, Ashton, & De Vries, 2011;Zettler & Hilbig, 2010). While the HEXACO model is becoming increasingly popular in I/O psychology (Hough & Connelly, 2013), as far as we are aware, there is no published study that has compared job applicants with non-applicants on the HEXACO model of personality.…”
Section: Hexaco Personalitymentioning
confidence: 99%
“…A survey of 341 work groups showed that at least six virtues are significantly related to the frequency of observed unethical behavior (Kaptein, 2011a). Other research showed a significant relationship between the virtues and whistle blowing (Kaptein, 2011b), engagement , commitment , absence due to illness (Kangas et al 2017), well-being (Huhtala et al 2011, delinquency (De Vries & van Gelder, 2015), and citizenship (Ruiz-Palomino & Martínez-Cañas, 2014).…”
Section: T H E C O R P O R a T E E T H I C A L Vi R T U E S Mo De Lmentioning
confidence: 99%
“…The CEV Model is derived from an analysis of 150 practices of unethical behavior. This analysis was the basis for seven relevant ethical virtues that were defined and subsequently tested (DeBode, Armenakis, Feild, & Walker, ; Kangas, Feldt, Huhtala, & Rantanen, ; Kaptein, ), and applied (De Vries & van Gelder, ; Huhtala & Feldt, ; Huhtala, Feldt, Lämsä, Mauno, & Kinnunen, ; Huhtala, Kangas, Lämsä, & Feldt, ; Huhtala, Kaptein, & Feldt, ; Huhtala, Tolvanen, Mauno, & Feldt, ; Kangas, Muotka, Huhtala, Mäkikangas, & Feldt, ; Kaptein, ; Riivari, Lämsä, Kujala, and Heiskanen, ; Ruiz‐Palomino & Martínez‐Cañas, ).…”
Section: Introductionmentioning
confidence: 99%